PENERAPAN MODEL PEMBELAJARAN NUMBER HEADS TOGETHER (NHT) PADA MATERI KEANEKARAGAMAN HEWAN DAN TUMBUHAN UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SD N 1 BEUREUNUEN - Zahrina (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2021)
This study aims to determine the improvement of student learning outcomes on the material diversity of animals and plants through the application of the Number Heads Together (NHT) learning model. This type of research is Classroom Action Research (CAR). The place of research is SDN 1 Beureunuen and carried out in the 2019/2020 academic year even semester. The research subjects were fourth grade students, totaling 34 students with heterogeneous abilities. Data collection techniques were carried out by observation, teacher observation sheets, student observation sheets, and evaluations. This research was carried out in three cycles and completed in cycle III. The results of observations showed that the acquisition of student learning outcomes with an average value in the first cycle: 65.73, the second cycle: 84.2 and the third cycle 93.97. The classical completeness score in the first cycle reached 35.29%, the second cycle reached 75.52%, and the third cycle reached 100%.